Analisis Perbandingan Hasil Belajar dan Berfikir Kritis Peserta Didik PAI Berdasakan Gender di SMA N 15 Bandar Lampung - Andyani, Aulia Rizki; Octafiona, Era; Istihana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to analyze differences in learning outcomes and critical thinking skills between male and female students in the subject of Islamic Religious Education and Character Education. The research employed a quantitative approach with a comparative method. The study participants were Grade XI students selected using purposive sampling techniques. Data on learning outcomes and critical thinking skills were collected through tests that had been validated and tested for reliability, and subsequently analyzed using comparative statistical tests. The results indicated significant differences in learning outcomes and critical thinking skills between male and female students in Islamic Religious Education and Character Education. Female students tended to achieve higher mean scores than male students. These findings suggest that gender is associated with students’ learning achievement and critical thinking abilities. The study concludes that it is important to implement learning strategies in Islamic Religious Education that are responsive to students’ differing characteristics in order to promote a more equitable and effective learning process.